Short Description of the Relevant Aspects of the Dutch Economy in the Global Economic System - Razvan Hagima (CES Working Papers, 2013)
Despite of its reduced population number and small area, the Netherlands is one of the top countries in terms of trade and FDI. The aim of this article is to present its trade, FDI flows and to highlight some of the advantages that the country has in the mentioned fields. Even though it was hit by the economic crisis, the state recovered fast and, since 2009, maintained a positive trend to its foreign trade and FDI. Moreover, because it has a stable economic environment and a professional labour force, foreign investors are eager to start investing in businesses in this country.
Keywords: F19; F63; O52; P45; 330; trade; FDI flows; investment projects; destination Romania